ANALISA PERENCANAAN TEKNIS PERHITUNGAN STRUKTUR BALOK DAN PLAT LANTAI MENGGUNAKAN SAP 2000 - Rizki Nurul Hakiki, Muhammad; Hendrayana, Yayat (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
The Silktown apartment project Alexandria tower has a number of 33 floors, 869 units is one of the apartment projects in the city to meet the needs of the megapolitan community for residential homes. This apartment is a community dream to have a modern residence with luxurious facilities. The structure used in the silktown Alexandria tower apartment construction project uses reinforced concrete structures with fc'35 MPa concrete quality and the quality of reinforcement in this project using Fy 400 Mpa (BJTD - 40)> D10 and Fy 240 Mpa (BJTP-24) <8 guideline for planning the structure of this project namely PPUIG 1983, SKSNI T-15-1991, SNI 03-2847-2002 and structural analysis using SAP2000 to calculate the loading that occurs with the final result in the form of Moment value, shear force is carried out regarding structural elements including: plate, beam and column. The results of the analysis and calculation of the structure will get how much reinforcement and inter-reinforcement distance needed in each structural element then described in accordance with the detailed reinforced concrete.